Material Familiarity and Aesthetic Learning in Early Childhood: A Mixed-Methods Study of Clay Art in Jepara, Indonesia - Ismintarti, Endar; Fajrie, Nur; Utaminingsih, Sri; Mustofa, Hisbulloh Als (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Screen-based engagement has increasingly displaced young children’s opportunities for tactile, embodied, and materially grounded learning. Within this context, clay-based art offers a potentially meaningful medium through which children can translate lived experience into three-dimensional expression, yet limited research has examined how children’s prior knowledge of a physical material relates to their artistic performance and emerging aesthetic learning. This study investigated children’s prior knowledge of clay, examined its relationship with artistic performance, and explored the forms of expression that emerged through clay-based artmaking. A mixed-methods sequential explanatory design was employed in Jepara Regency, Indonesia. In the quantitative phase, data were collected from 150 early childhood students using proportional stratified random sampling and analysed through descriptive statistics and analysis of variance (ANOVA). In the qualitative phase, 12 children were selected purposively for in-depth exploration through observation, interviews, field notes, and thematic analysis. The findings showed that children’s prior knowledge of clay was at a sufficient level and was strongly associated with artistic performance. The qualitative analysis further indicated that children’s artworks were shaped by three main experiential domains: the domestic environment, the local and natural environment, and media and personal imagination. Rather than treating clay as merely a motor activity, the study shows that clay-based artmaking can function as a situated form of aesthetic learning in which material familiarity, environmental exposure, and prior experience intersect. The study contributes to early childhood art education by offering a more grounded account of aesthetic learning as culturally mediated and materially situated, while also suggesting the pedagogical value of place-based and materially responsive art practices.